2016
DOI: 10.1155/2016/4918325
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Serum Cystatin C with Glomerular Filtration Rate in Patients Receiving Platinum-Based Chemotherapy

Abstract: Objectives. Serum cystatin C seems to be an accurate marker of glomerular filtration rate (GFR) compared to serum creatinine. The aim of this work was to explore the possibility of using serum cystatin C instead of serum creatinine to early predict renal failure in cancer patients who received platinum based chemotherapy. Design and Methods. Serum creatinine, serum cystatin C concentrations, and GFR were determined simultaneously in 52 cancer patients received carboplatin-based or cisplatin-based chemotherapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Early studies compared raw serum cystatin c and serum creatinine levels, without the use of estimation equations and determined that serum cystatin c was superior to serum creatinine in predicting 24‐h CrCl in a small sample of individuals with cancer 55 . However, serum cystatin c alone was also shown to have a much lower area under the curve than the CG for predicting renal failure in those receiving platinum‐based chemotherapy 56 . Cystatin c was subsequently introduced into GFR estimating equations.…”
Section: Estimated Gfr In Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies compared raw serum cystatin c and serum creatinine levels, without the use of estimation equations and determined that serum cystatin c was superior to serum creatinine in predicting 24‐h CrCl in a small sample of individuals with cancer 55 . However, serum cystatin c alone was also shown to have a much lower area under the curve than the CG for predicting renal failure in those receiving platinum‐based chemotherapy 56 . Cystatin c was subsequently introduced into GFR estimating equations.…”
Section: Estimated Gfr In Oncologymentioning
confidence: 99%
“…Cystatin c is increased by corticosteroid exposure, hyperthyroidism (decreases with hypothyroidism), and inflammation, all of which are prevalent in patients with cancer and may bias GFR estimations 57–59 . Some authors have proposed that chemotherapeutic agents may also influence cystatin c, though the data are limited and emerging evidence suggests that cystatin c is a reliable marker of kidney function in patients being treated with chemotherapy 55,56,60–63 . Furthermore, cystatin c levels may be susceptible to the presence of malignancy independent of renal function.…”
Section: Estimated Gfr In Oncologymentioning
confidence: 99%
“…Thus the serum level of cystatin C depends on the GFR, and it can be used as a measure of kidney function 24 . Within oncology, the use of isolated cystatin C measurements for the determination of GFR and detection of nephrotoxicity has been questioned, as there appear to be independent effects of both the malignancy and chemotherapy on cystatin C levels that confound its utility 25,26 …”
Section: Assessment Of Kidney Function In Patients With Cancermentioning
confidence: 99%
“…The narrow therapeutic indices of chemotherapeutics are one area where accurate kidney assessment is essential for medication safety and effectiveness. Studies with platinum-agents, particularly carboplatin, which are renally-eliminated and nephrotoxic, demonstrated that cysC predicted carboplatin area under the curve and clearance at least as well as SCr (R 2 for drug clearance 0.71 with SCr and 0.8 with cysC) [61,[70][71][72]. Use of cysC to more accurately predict drug clearance could spare patients dose-dependent adverse drug reactions such as carboplatin-induced thrombocytopenia [73].…”
Section: Malignancymentioning
confidence: 99%